Left hand financing : An emerging field of corporate finance - Chrystie, Thomas L., & Fabozzi, Frank J. (ed.); Fabozzi, Frank J. (ed.) (Illinious, USA : Dow Jones-Irwin, 1983)
This book is designed for the chief financial officer of a growth-oriented, asset-intensive corporation.
includes index
ijb, 11/10/2018
Loans
Keywords: Corporate finance